ANALISIS IMPLEMENTASI KURIKULUM IPS PADA JENJANG PENDIDIKAN DASAR - Abdul Manaf (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2018)
Talking about the concept of education cannot be separated from the curriculum. Because the competence of graduates has been decided, the necessary framework and scope of materials to be prepared to be learned and mastered by teachers as main actors of education as stated in Government Regulation No. 20, 2003 of the national education system, in chapter 19 verse one: that the curriculum is a set of plans and arrangements concerning the objectives, content, and materials and how are used as guidelines for learning activities to achieve specific educational goals. The concept of IPS education in this case is an idea that describes the relationship between two or more facts such as the concept of "human needs", which deals with a variety of things, such as clothing, food, safety, education, love, and prestige. The concept can also be interpreted as symbols or ideas created by the students to understand the experiences that occur repeatedly, social sciences (IPS) is not a field of study or discipline, but rather of a social problem and phenomena. Thus, IPS is the study of society and human– it is a social science which is derived from the social.